NASR HAMID ABU ZAYD AND THE HERMENEUTICAL OF QUR’AN - Wekke, Ismail Suardi; Firdaus, Acep (IAIN Tulungagung, 2018)
This paper discussed the life background of Nasr Hamid Abu Zayd and the hermeneutical method used to the interpretation of the Qur’an. Nasr Hamid Abu Zayd was among productive Muslim scientists. He wrote over twenty-nine works from 1964 to 1999. His works included books and articles. Nasr’sthought was a product of his educational background and religious thought. An interesting discussion of Nasr’s thought was the conceptual discourse(an-nash). In the historical trajectory of the Arabic world, the text had a crucial position, especially when we saw the development of Islamic literature from pre-Islamic to the Islamic era. The oral tradition was deeply rooted. The text was ultimately believed to have a major influence in the formation of civilization through a hermeneutical approach, developed by modernists such as Nasr Hamid Abu Zayd, which became an attempt to develop an approaching understanding the Qur’an which had been widely opposed among Muslims. Because there was a very basic difference between hermeneutics on the other hand, and tafsir-takwil on the other hand, so it is considered inappropriate to be used to study the Qur’an. Therefore, this paper will discuss the concept of the hermeneutical method of the Qur’an by Nasr Hamid Abu Zayd as a repertoire of Islamic studies.